Nursing care of patients who suffered from craniocerebral trauma and underwent surgical treatment - Sinkiewicz-Jaskólska, Renata; Jaskólski, Filip; Hagner, Wojciech; Dejewska, Jolanta; Grada, Justyna; Wiącek-Zubrzycka, Magdalena; Hagner-Derengowska, Magdalena (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Nursing care of a patient who suffered from craniocerebral trauma and underwent surgery treatment is to provide the patient with optimum conditions that will lead to a fast recovery and that will prevent any complications. Nursing management in the post-operative period includes mainly actions preventing respiratory, circulatory, cutaneous complications and infections, as well as the right placement of a patient after the surgery. Post-operative management also includes monitoring primary life parameters, controlling the state of post-operative wounds, fighting pain and mobilising a patient.